2020
DOI: 10.1016/j.joca.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

MFN2 contributes to metabolic disorders and inflammation in the aging of rat chondrocytes and osteoarthritis

Abstract: Objective: Metabolic disorders and inflammation of chondrocytes are major pathological changes in aging cells and osteoarthritis (OA). Recent studies demonstrated age-related mitochondrial dysfunction may be a key contributing factor in the development of OA. Mitofusin 2 (MFN2) is a key regulator of mitochondrial fusion, cell metabolism, autophagy and apoptosis. This study was performed to ascertain whether MFN2 was involved in the aging of chondrocytes and OA. Methods: Metabolic measurements were taken in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…MFN2 signaling is increased in senescent chondrocytes and osteoarthritic cartilage. Forced MFN2 expression worsens DMM-mediated articular cartilage injury, whereas knocking down the molecule delays OA conditions [48]. The investigations into Irisin downregulation of the mitochondrial fission reaction in inflamed chondrocytes also explained the protective actions of the myokine against mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…MFN2 signaling is increased in senescent chondrocytes and osteoarthritic cartilage. Forced MFN2 expression worsens DMM-mediated articular cartilage injury, whereas knocking down the molecule delays OA conditions [48]. The investigations into Irisin downregulation of the mitochondrial fission reaction in inflamed chondrocytes also explained the protective actions of the myokine against mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…Alterations in Mfn2 expression have also been observed in chronic neurodegenerative disorders, acute traumatic episodes such as stroke, and cardiometabolic diseases (Bach et al , 2003 ; Bach et al , 2005 ; Wang et al , 2009 ; Shirendeb et al , 2011 ; Marsboom et al , 2012 ; Martorell‐Riera et al , 2014 ). Given the well‐established role of Mfn2 as a regulator of mitochondrial metabolism (Bach et al , 2003 ; SebastiĂĄn et al , 2012 ; Schneeberger et al , 2013 ; Segales et al , 2013 ; Martorell‐Riera et al , 2014 ; Boutant et al , 2017 ; Tur et al , 2020 ; Xu et al , 2020 ) and the importance of mitochondrial metabolism in the physiopathology of these disorders, understanding the bioenergetic mechanism of Mfn2 may aid in the design of therapeutic approaches for disorders in which Mfn2 is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the discovery of mitofusins, it was observed that expression of Mfn2 maintains mitochondrial bioenergetics more efficiently than expression of Mfn1, despite Mfn1 being more efficient at mediating mitochondrial fusion (Bach et al , 2003 ; Eura et al , 2003 ; Ishihara et al , 2004 ). Diminishment of Mfn2 expression as well as Mfn2 deletion have been shown to reduce mitochondrial respiration in different cell types (Bach et al , 2003 ; SebastiĂĄn et al , 2012 ; Schneeberger et al , 2013 ; Martorell‐Riera et al , 2014 ; Boutant et al , 2017 ; Li et al , 2019 ; Tur et al , 2020 ; Xu et al , 2020 ), including fibroblasts (Yao et al , 2019 ; Hu et al , 2020 ). However, Kawalec et al ( 2015 ) have reported increased oxygen consumption in Mfn2 KO MEFs, although they did not observe changes in RCR and found reduced MMP and mitochondrial ATP production, concluding that Mfn2 KO MEFs have impaired bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…A similar role has been shown in murine cultured neurons [ 100 ]. In chondrocytes, an age dependent reduction of MFN2 causes a reduction in mitochondrial fission, accompanied by dysfunctional mitochondria and oxidative stress [ 101 ]. Interestingly, in this model Parkin negatively regulates the levels of MFN2, and an age-related decrease of Parkin causes a post transcriptional increase of MFN2 and hyperfused mitochondria.…”
Section: Mitophagy and Oxidative Stress In Physiological Agingmentioning
confidence: 99%
“…MFN2 expression is higher in rat and human chondrocytes during aging and OA (osteoarthritis) [ 101 ]…”
Section: Figurementioning
confidence: 99%